2022
DOI: 10.21608/ejabf.2022.273357
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric characterization of four cichlid species from River Nile and Lake Burullus populations, Egypt

Abstract: SD= Standard Deviation. Means with different letters in the same rows are significantly different (Duncan test, P ≤ 0.05); a < b < c < d; abbreviations of morphometric ratios were previously recorded in materials & methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Therefore, the eye diameter can serve as a basis of differentiating this putative hybrid from other tilapine species found in the lagoon. The mean values obtained in this study for AFL, HL, BD and CPL fits within the range reported for Copton zilli by [24]. The mean values of most morphometric measurements in the putative hybrid were higher than that of the O. niloticus except in PDD, POL, LaRL, IOD, VFL, and PPFL.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the eye diameter can serve as a basis of differentiating this putative hybrid from other tilapine species found in the lagoon. The mean values obtained in this study for AFL, HL, BD and CPL fits within the range reported for Copton zilli by [24]. The mean values of most morphometric measurements in the putative hybrid were higher than that of the O. niloticus except in PDD, POL, LaRL, IOD, VFL, and PPFL.…”
Section: Discussionsupporting
confidence: 87%